Efektivitas Influencer Marketing dan User-Generated Content dalam Meningkatkan Loyalitas Konsumen Produk Wirausaha Muda di Era Digital - Dewi Rawa, Ricola; Hendharsa, Angga; Arweni, Arweni; Mursalin, Adi (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the influence of influencer marketing and user-generated content (UGC) on consumer loyalty toward young entrepreneurs' products in the digital era. Using a quantitative approach with SEM-PLS techniques, data were collected from 300 respondents in Pontianak City. Results show that both influencer marketing and UGC have a significant effect on consumer loyalty. These findings indicate that integrating these two digital marketing strategies is effective in strengthening consumer loyalty and provides strategic implications for the sustainable development of MSMEs in the digital era.